Performance evaluation of GPS receiver under equatorial scintillation - Moraes,Alison de Oliveira (2009)
Abstract: Equatorial scintillation is a phenomenon that occurs daily in the equatorial region after the sunset and affects radio signals that propagate through the ionosphere. Depending on the temporal and spatial situation, equatorial scintillation can represent a problem in the availability and precision of the Global Positioning System (GPS). This work is concerned with evaluating the impact of equatorial scintillation on the performance of GPS receivers. First, the morphology and statistical model of equatorial scintillation is briefly presented. A numerical model that generates synthetic scintillation data to simulate the effects of equatorial scintillation is presented. An overview of the main theoretical principles on GPS receivers is presented. The analytical models that describe the effects of scintillation at receiver level are presented and compared with numerical simulations using a radio software receiver and synthetic data. The results achieved by simulation agreed quite well with those predicted by the analytical models. The only exception is for links with extreme levels of scintillation and when weak signals are received.